Treatment challenges of nevirapine-induced Stevens-Johnson syndrome: a case report - Rosandy, Milanitalia Gadys; Indiastari, Dewi; Candradikusuma, Didi; Budiarti, Niniek; Sutanto, Heri; Amalia, Dinda (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Nevirapine, a non-nucleoside reverse transcriptase inhibitor (NNRTI), is a crucial component of antiretroviral therapy (ART) in HIV management. However, nevirapine carries a rare but potentially life-threatening risk of Stevens-Johnson syndrome (SJS). We reported a case of severe cutaneous manifestations of extensive necrolysis in an HIV-positive patient on the ARV nevirapine. This case highlights the importance of recognizing nevirapine-induced SJS, particularly in the early stages, to ensure prompt discontinuation of the drug and initiation of appropriate supportive care. Clinicians managing HIV patients on nevirapine-based ART should remain vigilant for early signs of SJS and maintain a high index of suspicion.